General practitioners’ perceptions of heat health impacts on the elderly in the face of climate change: a qualitative study in Baden-Württemberg, Germany - Herrmann, Alina; Sauerborn, Rainer (International journal of environmental research and public health, 2018)
Heat health impacts (HHI) on the elderly are a growing concern in the face of climate change and aging populations. General practitioners (GPs) have an important role in health care for the elderly. To inform the development of effective prevention measures, it is important to investigate GPs’ perceptions of HHI. Twenty four qualitative expert interviews were conducted with GPs and analyzed using the framework approach. GPs were generally aware of heat health impacts, focusing on cardiovascular morbidity and volume imbalances. Perceptions of mortality and for instance impacts on respiratory diseases or potentially risky drugs in heat waves partly diverged from findings in literature. GPs judged the current relevance of HHI differently depending on their attitudes towards: (i) sensitivity of the elderly, (ii) status of nursing care and (iii) heat exposure in Baden-Württemberg. Future relevance of HHI was perceived to be increasing by most GPs. The main cause identified for this was population aging, while impacts of climate change were judged as uncertain by many. GPs’ perceptions, partly diverging from literature, show that GPs’ knowledge and awareness on HHI and climate change needs to be strengthened. However, they also emphasize the need for more research on HHI in the ambulant health care setting. Furthermore, GPs perceptions suggest that strong nursing care and social networks for elderly are major elements of a climate resilient health system.
Gesehen am 05.06.2018